Room temperature kerfless silicon thin foils obtained via a stress inducing epoxy layer. Issue 11 (17th September 2014) - Serra, João; Bellanger, Pierre; Bouchard, Pierre O.; Bernacki, Marc; Pizzini, Sergio; Kissinger, Gudrun
Abstract We present 5 × 5 cm2 SLIM‐cut foils obtained by cooling form curing temperatures of 150 °C to room temperature using an epoxy stress inducing layer. Numerical simulations were performed to help the definition of an optimum geometry and we demonstrate the capability to obtain several thin foils from the same substrate. The evolution of minority carrier lifetime upon successive exfoliation of the same substrate is presented. Measured lifetimes in these silicon foils increase after etching suggesting that recombination centers are present close to the foil surface. Effective lifetimes of 50 microseconds were obtained in 120 µm thick foils, corresponding to diffusion length much larger than the foil thickness. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)